The effect of harvest date on the chemical composition, gross energy, organic matter digestibility, nutritive value and amino acid content of white lupin (Lupinus albus L.) - Peiretti, P. G.; Dapr?, F.; Zunino, V.; Meineri, G. (Cuban Journal of Agricultural Science, 2010)
The aim of this study was to determine the chemical composition, gross energy (GE), organic matter digestibility (OMD), nutritive value and amino acid content of white lupin (Lupinus albus L.) during its growth cycle. Herbage samples were collected four times at progressive morphological stages from the late bud to the young green pod stage. Two replications were performed at each stage and all data are mean values of the triplicate analyses performed for each sample. The variability in the herbage quality characteristics were analysed for their statistical significance via analysis of variance to test the effect of the growth stage. The dry matter (DM) and fibrous fractions increased during maturation. No significant differences were found in organic matter (OM), ash and ether extract. The GE content ranged from 17.3 to 17.7 MJ/kg DM, while the crude protein, OMD and net energy for lactation declined with advancing maturity from 140 to 131 g/kg DM, from 693 to 615 g/kg OM and from 5.5 to 4.9 MJ/kg DM, respectively. The relative proportions of the individual amino acids (AA) and total AA were unaffected by the harvest date. Aspartic and glutamic acid were the two most abudant AA in the plant during growth. White lupin forage harvested at the flowering stage provides good quality forage for ruminants and could help improve the self-sufficiency of dairy farms, in terms of home-grown protein forages. Further studies are necessary to determine the DM yield of the crop and the intake of this forage by ruminants. Key words: Lupinus albus, nutritive value, quality, forage, morphological stage